2012
DOI: 10.2196/jmir.2100
|View full text |Cite
|
Sign up to set email alerts
|

Motivators and Motivations to Persist With Online Psychological Interventions: A Qualitative Study of Treatment Completers

Abstract: BackgroundMany users of Internet interventions do not persist with the full treatment program. As persistence may influence outcomes of such interventions, being able to maximize persistence is vital. However, while studies have begun to explore the predictors of dropout in Internet interventions, few have explored reasons why users persist with the programs, which may not just be the converse of the reasons for dropout.ObjectiveTo answer the question of what influences persistence with online interventions.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
192
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(213 citation statements)
references
References 56 publications
18
192
2
1
Order By: Relevance
“…Women expressed a desire for information on parenting in the context of PND, managing the transition to motherhood, content on communication and eliciting support, managing maternal sleep in the postnatal period, and anxiety, particularly social anxiety as it impacted on women's ability to integrate with other new mothers. Treatments that include a wide variety of treatment examples, modular and/or adaptive content can help ensure that individuals can personalize materials (Donkin and Glozier, 2012). This will help ensure that women are able to immediately access treatment relevant content.…”
Section: Discussionmentioning
confidence: 99%
“…Women expressed a desire for information on parenting in the context of PND, managing the transition to motherhood, content on communication and eliciting support, managing maternal sleep in the postnatal period, and anxiety, particularly social anxiety as it impacted on women's ability to integrate with other new mothers. Treatments that include a wide variety of treatment examples, modular and/or adaptive content can help ensure that individuals can personalize materials (Donkin and Glozier, 2012). This will help ensure that women are able to immediately access treatment relevant content.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study (Watts et al, 2013) comparing a depression program via mobile phone to a program via computer showed that slightly more participants using the computer (64% versus 54%) endorsed the program stating that they were 'very satisfied', with the remaining participants endorsing 'somewhat satisfied'. Donkin and Glozier (2012) focused on adherence and motivation in their study on internet-based treatment for depression in persons with risk of cardiovascular disease and found that content which enhances motivation such as having a sense of control and being able to identify with the program could be useful as well as increasing the relative value of the treatment program in order to enhance persistence. A meta-synthesis of qualitative studies revealed a number of themes, including the nature of personal experience in depression; help-seeking in primary care; control and helplessness in engagement with treatment; stigma associated with treatment; and patients' understandings of self-help interventions (Khan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The meaningful experience is closely related to the concept of engagement which is seen as an important predictor of both adherence to online interventions and the effectiveness of these interventions [12,14,42]. This study is a first step in uncovering how gamification, and design in general, may enhance motivation in the context of psychological online interventions and offers a starting point for creating engaging interventions.…”
Section: Resultsmentioning
confidence: 95%
“…More recently, it has been posited that just adherence (i.e. using the intervention as intended by the developers) may nog be enough for an intervention to be effective, but that it is also necessary for participants to feel involved with an intervention, or to be able to identify with the intervention [12,13]. Together, these factors may be called engagement, i.e.…”
Section: Introduction Backgroundmentioning
confidence: 99%